The Bethesda System for Reporting Thyroid Cytopathology: Validating at Tribhuvan University Teaching Hospital - Acharya,Kunjan (2022)
Abstract Introduction Fine needle aspiration cytopathology (FNAC) is widely used for the stratification of thyroid nodules. Objective The objective of the present study is to validate FNAC reporting based on The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) at our institution and to calculate the risk of malignancy in each category. Methods This was a descriptive cross-sectional study conducted jointly at the Department of Ear, Nose and Throat and at the Department of Pathology for a period of 1.5 years (May 2018 to November 2018). All cases presenting with thyroid swelling in the outpatient department were investigated with ultrasonography (USG) of the neck, thyroid function test, and FNAC. All FNAC reporting was done according to TBSRTC. Results A total of 134 thyroidectomies were performed during the study period. The female to male ratio was 5.3:1. The age ranged from 11 to 74 years old. with a mean age of 51 years old. The FNAC has a specificity of 84.9%, a sensitivity of 89.4%, a positive predictive value of 86.4%, a negative predictive value of 88.2%, and an accuracy of 87.3% in detecting thyroid cancer. The implied risk of malignancy (ROM) in Bethesda II, III, IV, V and VI is 11.7%, 25%,40%,76.6% & 96%, respectively. Conclusion The four studied categories had a ROM comparable to other studies, except for the Bethesda III category. Further studies with larger sample sizes and with the use of USG guidance for the aspiration from the thyroid swelling may give better results by reducing the number of false negative and false positive cases.